Penegakan Hukum terhadap Pelaku Usaha Pom Mini di Desa Gelung Kecamatan Paron Kabupaten Ngawi - Widha Ari Febriani; Diah Ratna Sari Hariyanto (Syntax Corporation Indonesia, 2024)
This research aims to determine law enforcement against mini pom business actors in Gelung Village, Paron District, Ngawi Regency along with the obstacles and efforts. This research uses descriptive analytical reseearch with a normatiive approach methodology. The results ofthis research is the effectiveness of law enforcement against Mini Pom Business Actors in Gelung Village is currently still not optimal. The problem is include the small number of Paron Police Criminal Investigation Unit personnel, making it difficult to carry out operations and patrols. Besides that, the lack of legal knowledge among fuel traders in the Gelung Village area has resulted in an increasing number of fuel traders running their businesses without permits, making law enforcement difficult. Preventive efforts are undertaken, including cooperative outreach with local government representatives to raise awareness of the significance of business permits for gasoline trade. Enhancing oversight of fuel trade businesses (mini pumps) within Paron District's jurisdiction, particularly in Gelung Village. to lessen the room available for business actors to establish companies without authorization. imposes penalties on those who open a business without a permit, including fines and jail.